Utilization of Waste Textile Cotton by Synthesizing Sodium Carboxymethyl Cellulose: An Approach to Minimize Textile Solid Waste - Md. Samsur Rahaman; Sultana Shamsun Nahar; Jahid M. M. Islam; Rajib Samadder; Md. Saifur Rahaman; Rujina Khatun Chadni; Faisal Rahaman Shagor; Md. Latifur Rahman; Tania Akter Ruhane; Mubarak Ahmad Khan (Advances in Polymer Technology)
This research uses waste textile cotton (WTC) from the textile industry as a raw material to synthesize sodium carboxymethyl cellulose (CMC) by adapting a modified etherification methodology. Yields of technical CMC (TCMC), semipurified CMC (SPCMC), and purified CMC (PCMC) were 3.45±0.17 g, 2.49±0.08 g, and 1.51±0.016 g, respectively, per gram of cotton waste. Degree of substitution (DS) values of PCMC, SPCMC, and TCMC was 0.998±0.007, 0.79±0.031, and 0.561±0.029, respectively. For PCMC, SPCMC, and TCMC, the purity of the prepared different grades of CMC was 98.59±0.12%, 78.56±1.93%, and 61.59±2.31%, respectively. Fourier transform infrared spectroscopy (FTIR) peak values were 3437 cm-1, 1609 cm-1, and 1427 cm-1, proving WTC conversion to CMC. Furthermore, 2θ values of X-ray diffraction (XRD) peaks were 9.7 and 20.5, confirming the transformation of WTC to CMC as well. Thermogravimetric analysis (TGA) and scanning electron microscope (SEM) have been assessed to define CMC’s thermal stability and morphology, respectively.